Factors influencing preformed metal crowns and prefabricated zirconia crowns - Shuman Deng; Weiwei Dou; Ying Chen; Zhixiao Chen; Ning Song; Qi Gao; Li Zhang; Jing Xie (BMC Oral Health)
Abstract Backgound Preformed metal crowns (PMCs) and zirconia crowns (ZCs) are commonly used for the treatment of primary molar caries. However, there have been no reports on factors influencing parental awareness, willingness to use these treatments, and the associated discomfort after crown placement in children.This study is the first to report factors influencing preformed crowns, providing a reference for the prevention and treatment of deciduous carious teeth. Methods Parents whose children’s posterior caries were restored with preformed crowns at Shenzhen Children’s Hospital from October 2021 to October 2023 were recruited. A questionnaire gathered data on multiple variables, including basic information about the participants, their oral health behaviors, and their attitudes toward oral health. Results Approximately two-thirds of the surveyed parents were aware of preformed metal crowns (PMCs) (67.8%), whereas over half were hardly aware of prefabricated zirconia crowns (ZCs) (59.6%). In terms of discomfort symptoms, 105 (76.7%) and 102 (76.1%) cases were reported after PMC and ZC placement respectively; however, there was no statistically significant difference between the two groups (P > 0.05). Among the surveyed parents, 19 (8.7%) expressed that they could not accept the PMC color, whereas all could accept the ZC color, and the difference was statistically significant (P < 0.05). A total of 217 parents (99.5%) could accept PMCs to protect or repair primary carious teeth; 29.8% of the parents stated that they were reluctant to use ZCs to protect or repair their children’s deciduous teeth, and the difference was significant (P < 0.05). In terms of location selection, the majority of surveyed parents chose comprehensive hospitals (58.7%) and stomatological hospitals (41.3%). In terms of institution selection, priority was given to the doctor’s qualifications (90.4%). Pearson correlation analysis revealed that “acceptance of the PMC color”, “oral health awareness”, and “parental willingness to use PMCs” were positively correlated (P < 0.05) and that “non-nuclear family status” was negatively related to “parental willingness to use PMCs” (P < 0.05). The logistic multiple regression analysis revealed that oral health awareness and restoration awareness significantly affected the duration of discomfort symptoms after PMC placement (P < 0.15). Children with higher annual family incomes, families with fewer children, lower consumption of desserts, better oral health awareness, and teeth brushing under the assistance of their parents showed a dramatic decline in untimely PMC repair (P < 0.15); children who brushed their teeth less and whose parents had a poorer perception of restoration methods showed an increase in untimely PMC repair (P < 0.15). Conclusions This discrepancy is reflected in the cognition and willingness to use PMCs and ZCs. PMCs are more accepted due to cost, whereas ZCs are preferred for aesthetics. The factors affecting PMC restoration are oral health awareness, manner of restoration, family income, number of children, consumption of desserts, and toothbrushing frequency.